Lazarus (2013): sourcebook collection, volume 1 ebook - Bailey, Neal (Lazarus (2013), 2018)
Collecting the first three LAZARUS SOURCEBOOKS, covering the lands ruled by Carlyle, Hock, and Vassalovka, now in one volume. With revised and expanded content, including additions to reflect developments in LAZARUS as the series moves into the year X+67 with FRACTURE,î beginning summer of 2018. Author: Greg Rucka, Neal Bailey, David Brothers, Robert Mackenzie, Gareth-Michael Skarka, Eric Trautmann, Michael Lark. Illustrator: Owen Freeman . 2018 Greg Rucka and Michael Lark.